The impact of the ICT training program on the attitudes of physics teachers towards e-learning, an experimental research (Journal of the College of Basic Education, 2023)
Education has general and specific goals that it seeks to achieve through its institution, and the most important of these institutions is the school and its elements, and the first of these elements is the teacher that education adopts for the circulation of other elements. Therefore, attention should be paid to preparing him before service and training him during service in a correct and appropriate manner, so that he can keep abreast of developments in the field and achieve goals.One of the best ways to keep pace with these contexts and their methods is to increase the efficiency of educational bodies, and the most prominent way to increase these competencies is to train teachers to adopt modern teaching methods to improve their performance and raise the level of their students in the emotional, skill and knowledge aspects.